184 Association between high-sensitivity troponin and one year mortality in 20, 000 consecutive hospital patients undergoing a blood test for any reason. (4th June 2021) - Hinton, Jonathan; Mariathas, Mark; Gabara, Lavinia; Allan, Rick; Nicholas, Zoe; Kwok, Chun Shing; Ramamoorthy, Sanjay; Calver, Alison; Corbett, Simon; Rawlins, John; Simpson, Iain; Wilkinson, James; et al.
Abstract : Introduction: High sensitivity troponin (hs-cTn) concentrations above the manufacturer recommended upper limit of normal (ULN) are seen frequently in patients without a clinical presentation consistent with an acute coronary syndrome. There is increasing evidence that these concentrations may act as a marker of prognosis in a range of conditions. However, previous studies have been limited because they have only included patients in whom the clinician has requested the test. The aim of this study was to assess the relationship between one year mortality and hs-cTn concentration in a consecutive hospital population, regardless of whether there was a clinical indication for performing the test. Method: This study included 20, 000 consecutive patients that had hs-cTnI added onto their blood tests at a large teaching hospital, regardless of the clinical indication (CHARIOT population). One year mortality data was obtained by linkage with NHS Digital. The association between hs-cTnI concentration and one year mortality was evaluated using Kaplan-Meier plots and Cox proportional hazards analyses. After the cohort was considered as a whole, each of the clinical areas (inpatient (IPD), outpatient (OPD), emergency department (ED)) were considered separately. Results: Overall, 1782 (8.9%) patients had died at one year. Multivariable Cox regression analysis showed that a hs-cTnI concentration above the ULN was independently associated with the hazard of mortality (HR 2.23; 95% CI 1.97 – 2.52). There was a progressive increase in mortality across the strata of hs-cTnI concentration ( figure 1 ). Furthermore the log (10) hs-cTnI concentration was an independent predictor of the hazard of one year mortality (HR 1.77; 95% CI 1.64 – 1.91). The discriminative ability of hs-cTnI for one year mortality was good with an AUC of 0.75 (95%CI 0.73 – 0.76). Further, the log(10) hs-cTnI concentration was independently associated with mortality across all three locations and most strongly in the OPD cohort (IPD HR 1.49; 95% CI 1.33 – 1.67, OPD HR 2.44; 95% CI 1.95 – 3.04, ED HR 1.99; 95% CI 1.76 – 2.25). Conclusion: In a large, unselected hospital population of both in- and out-patients, 18, 282 (91.4%) of whom there was no clinical indication for testing, hs-cTnI concentration was independently associated with one year mortality. These data suggest that hs-cTnI may have a role as a biomarker of future risk. Conflict of Interest: Beckman Coulter paid for all of the assays used in our studies but had no other role in the studies